QR-313, an antisense oligonucleotide, shows therapeutic efficacy for treatment of dominant and recessive dystrophic epidermolysis bullosa: a preclinical study - Bornert, Olivier; Hogervorst, Marieke; Nauroy, Pauline; Bischof, Johannes; Swildens, Jim; Athanasiou, Ioannis; Tufa, Sara F.; Keene, Douglas R.; Kiritsi, Dimitra; Hainzl, Stefan; Murauer, Eva M.; Marinkovich, M. Peter; et al. (The journal of investigative dermatology, 2021)
Dystrophic epidermolysis bullosa (DEB) is a blistering skin disease caused by mutations in the gene COL7A1 encoding collagen VII. DEB can be inherited as recessive DEB (RDEB) or dominant DEB (DDEB) and is associated with a high wound burden. Perpetual cycles of wounding and healing drive fibrosis in DDEB and RDEB, as well as the formation of a tumor-permissive microenvironment. Prolonging wound-free episodes by improving the quality of wound healing would therefore confer substantial benefit for individuals with DEB. The collagenous domain of collagen VII is encoded by 82 in-frame exons, which makes splice-modulation therapies attractive for DEB. Indeed, antisense oligonucleotide-based exon skipping has shown promise for RDEB. However, the suitability of antisense oligonucleotides for treatment of DDEB remains unexplored. Here, we developed QR-313, a clinically applicable, potent antisense oligonucleotide specifically targeting exon 73. We show the feasibility of topical delivery of QR-313 in a carbomer-composed gel for treatment of wounds to restore collagen VII abundance in human RDEB skin. Our data reveal that QR-313 also shows direct benefit for DDEB caused by exon 73 mutations. Thus, the same topically applied therapeutic could be used to improve the wound healing quality in RDEB and DDEB.
Das PDF enthält zusätzlich einen Anhang von 6 Seiten (893.e1-893.e6)
Corrected proof published online 17 November 2020
Gesehen am 10.05.2021